Must Gandhi fall? Insurrections Ensemble and the Gandhi Project: Living Rights Festival - Sitas, Ari (New Agenda: SA Journal of Social and Economic Policy, 2025)
Many people have asked me in a rather bewildered tone, what was it that we staged during the Living Rights Festival at the Avalon Theatre at the District Six Homecoming Centre in Cape Town? The performance was not a play but felt like one! It was not a political statement although it sounded like one, it was not a musical but it was full of music and it was not an art work but it was full of art! And it was about Gandhi without Gandhi appearing on stage once!